Barriers and enablers in risk management practices in construction industry amongst bumiputera contractors - Fadzil, Nur Syuhada (2021)
Nowadays, an important process in a construction project’s success is risk management because it can reduce or remove adverse occurrences that can affect the aims of the construction project in terms of safety, quality and delay. In the Malaysian construction industry, the application of risk management is at a low level, where it is executed in traditional ways, which are brainstorming and checklists. These are due to the high cost of hiring experts, lack of knowledge and avoiding extra costs. The aim of this study was to develop a framework of the relationship between the barriers and enablers in risk management practices. To achieve the aim, three objectives were laid out, which were identifying the significant barrier factors in risk management practices, identifying the significant enabler factors in risk management practices and develop the structural relationship between the barriers and enablers in risk management practices. The method used in this study was the quantitative research method, wherein data were collected using a questionnaire survey. An actual survey was carried out by distributing questionnaire forms to Bumiputera contractors in Johor. The outcome of the responses from 34 respondents of the actual survey indicated that all barrier and enabler factors had a Cronbach’s alpha value of more than 0.796 and 0.839. Therefore, the consistency of the data was high. The data were then applied for factor analysis. Next, the data were used to develop a structural relationship model of the barrier and enabler factors using SmartPLS software. As identified in the model, it was found that the group factor which has the highest impact on the barriers and enablers in risk management issues with a path coefficient β-value of 3.287 is Management initiative (CE), which comes from the Lack of knowledge (CB) group. Identifying these factors could provide awareness for Bumiputera contractors in identifying potential barriers and enablers in the implementation of risk management practices when handling their construction projects.